2014
DOI: 10.1002/hep.26763
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP-ribose) polymerase-1 is a key mediator of liver inflammation and fibrosis

Abstract: Poly (ADP-ribose) polymerase 1 (PARP-1) is a constitutive enzyme, the major isoform of PARP family, which is involved in the regulation of DNA repair, cell death, metabolism, and inflammatory responses. Pharmacological inhibitors of PARP provide significant therapeutic benefits in various preclinical disease models associated with tissue injury and inflammation. However, our understanding the role of PARP activation in the pathophysiology of liver inflammation and fibrosis is limited. In this study we have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 28 publications
(49 reference statements)
4
110
0
Order By: Relevance
“…The mechanism of the anti-fibrotic effects of puerarin involves its ability to inhibited expression of PARP-1, which is a novel mediator of CCl 4 -induced chronic liver fibrosis as demonstrated recently [43]. The certain role between PARP-1 activation and the profibrotic gene expression such as TGF-b and CTGF has been reported in vascular smooth muscle cells [44].…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of the anti-fibrotic effects of puerarin involves its ability to inhibited expression of PARP-1, which is a novel mediator of CCl 4 -induced chronic liver fibrosis as demonstrated recently [43]. The certain role between PARP-1 activation and the profibrotic gene expression such as TGF-b and CTGF has been reported in vascular smooth muscle cells [44].…”
Section: Discussionmentioning
confidence: 95%
“…Ligation of the common bile duct was performed as described previously (67). Average survival was 18–20 days after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were cut at 4-μm thickness for staining, and staining was performed as described previously (67). …”
Section: Methodsmentioning
confidence: 99%
“…In acute liver injury induced by CCl 4 , there were drastic decreases in the activities of the main liver P450 isoenzymes such as CYP1A2, CYP2C6, CYP2E1 and CYP3A2, as well as their protein expressions due to oxidative stress [30]. And chronic CCl 4 -induced liver injury was also characterized by dysregulation of numerous genes involved in metabolism [31]. In this study, considerable decreases in hepatic CYP3A and CYP2E1 protein level were found in rats treated with CCl 4 alone.…”
Section: Discussionmentioning
confidence: 99%